New Method of Parent Catheter Advancement in the Balloon Anchor Technique during Balloon-Occluded Transarterial Chemoembolization for Hepatic Tumors - Kei Shibuya; Hiroki Tahara; Suguru Takeuchi; Yoshinori Koyama; Yoshito Tsushima (Case Reports in Radiology)
Balloon-occluded transarterial chemoembolization (B-TACE) using a microballoon catheter is a promising method for improvement of lipiodol emulsion accumulation and local control relative to conventional transarterial chemoembolization. This method has been referred to as the balloon anchor technique in previous reports. We report a new technique for successful parent catheter advancement for achievement of stable backup for the selective insertion of a microballoon catheter during B-TACE using the microballoon as an anchor, even in patients with tortuous anatomy of the hepatic and celiac arteries. Deep cannulation of parent catheters was accomplished in all three cases and complications such as vascular injury were not observed in the postprocedure angiograms.